Survey of Traffic Engineering Solution for Telecommunication Network Optimization - Ahmad M. Hailan; Hisham Alshaheen (Tikrit Journal of Engineering Sciences)
Telecommunication network operators face many challenges, including network congestion, service quality, and network reliability. This study explores a solution that may mitigate these challenges. The suggested traffic engineering solutions for telecommunication network optimization are a comprehensive review of various traffic engineering techniques and tools used to optimize the performance of telecommunication networks. The survey analyzes the principles of Quality of Service (QoS), Traffic Engineering (TE), and Network Planning and Optimization (NPO). These principles aim to find acceptable solutions to improve network performance, reduce latency and packet loss, and enhance user experience by providing higher bandwidth and better network coverage. The study also investigates the role of emerging technologies, such as software-defined networking (SDN) and network function virtualization (NFV), in traffic engineering and optimization. These technologies offer new opportunities for traffic management and network automation, enabling network operators to deploy traffic engineering solutions efficiently and effectively. It emphasizes the need for more advanced traffic engineering solutions that can cope with the growing complexity of telecommunication networks. Especially the increasing demand for high-speed connectivity and the diverse range of tools and services offered over the network. The survey concludes by highlighting the key challenges and future directions of traffic engineering in telecommunication networks.